The Correlation Between Mother's Knowledge And Husband's Support On Contraception Use In sri Tawang Sapto Hastuti, Amd.keb Maternal Clinic of Surabaya - Reza Vebi Arisma; Luluk Khusnul Dwihestie (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Based on Surabaya BKKBN data for 2020, short-term contraception users reached 58.6%, but long-term contraception users were only around 23.3%. The use of long-term contraception must be increased in an effort to reduce rates of infertility, abortion, pregnancy protection, and death. To become an acceptor of long-term contraception, a woman must have good knowledge and have the support of their husbands. This study aims to determine the relationship between mother's knowledge and husband's support with contraceptive use. This type of research is quantitative research with a correlational design with a cross sectional approach. The study population was couples of childbearing age at PMB Sri Tawang SH at A.Md.Keb Surabaya. The sampling technique used probability sampling, obtained a sample of 60 respondents. The research instrument used a questionnaire. Data analysis used the chi-square statistical test. The results of this study indicate that there is a relationship between maternal knowledge and contraceptive use (p-value 0.000 and closeness value 0.397), and there is a relationship between husband's support and contraceptive use (p-value 0.000 and closeness value 1.000). The conclusion of this study is that there is a relationship between mother's knowledge and husband's support with contraceptive use. It is recommended that couples of childbearing age can increase their knowledge about various type of contraceptive methods according to their needs.